The Effect of Work Performance and Employee Loyalty on Promotion at the Nuances of Independent Women's Cooperative in Semarang - Fidyah Yuli Ernawati; Heni Subekti (Cita Konsultindo Research Center, 2024)
Human resource management is currently the most important factor and asset of a company. This study aims to determine the Effect of Work Performance and Employee Loyalty on Promotion at the Nuansa Mandiri Women's Cooperative in Semarang. The independent variable is Job Performance (X1), Employee Loyalty (X2), and the dependent variable is Promotion (Y). The population of this study was all employees of the Nuansa Mandiri Women's Cooperative in Semarang amounting to 302 people and for the sample using the Simple random sampling technique it was known to be 75 people. Data collection techniques are quantitative methods using questionnaires. For instrument testing using Validity test, Reliability test, and classical Assumption test. For data analysis techniques using multiple linear regression analysis methods with t test, Model Feasibility test and Coefficient of Determination (R2). The results of the study using multiple linear regression showed the regression equation as follows: Y = 7.040 + 0.342X1 + 0.323X2. From the t test, it is known that for the Job Performance variable (X 1) a calculated t value of 2.833 is obtained with a significance level of 0.000, because t count 2.833 > t table 1.665; significance is less than 0.05 (0.006<0.05), then the Job Performance variable has a positive and significant effect on promotion, the variable Employee Loyalty (X2) obtained a calculated t value of 2.979 with a significance level of 0.000, because t count 2.979> t table 1.665; significance is less than 0.05 (0.004<0.05), then the variable Employee Loyalty has a positive and significant effect on promotion. The main advice for company leaders is expected to pay attention to the work performance of employees, in this case company leaders must encourage employees in carrying out work willing to do overtime hours if there is work that has not been fully completed.